2010
DOI: 10.5194/acp-10-4977-2010
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the reversible uptake of chemical species in the gas phase by ice particles formed in a convective cloud

Abstract: Abstract. The present paper is a preliminary study preparing the introduction of reversible trace gas uptake by ice particles into a 3-D cloud resolving model. For this a 3-D simulation of a tropical deep convection cloud was run with the BRAMS cloud resolving model using a two-moment bulk microphysical parameterization. Trajectories within the convective clouds were computed from these simulation outputs along which the variations of the pristine ice, snow and aggregate mixing ratios and concentrations were e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…This might be due to the use in our study of a double moment microphysical scheme and a budget calculation time step of 5 min instead of a single moment scheme. Marécal et al (2010) have shown in a convective cell simulation that the amount of ice of the cell core was higher for a single moment microphysical scheme than for a similar simulation using a double moment microphysical scheme. Another possible explanation is a difference in the vertical velocities computed in each simulation.…”
Section: Chad Casementioning
confidence: 99%
“…This might be due to the use in our study of a double moment microphysical scheme and a budget calculation time step of 5 min instead of a single moment scheme. Marécal et al (2010) have shown in a convective cell simulation that the amount of ice of the cell core was higher for a single moment microphysical scheme than for a similar simulation using a double moment microphysical scheme. Another possible explanation is a difference in the vertical velocities computed in each simulation.…”
Section: Chad Casementioning
confidence: 99%
“…CATT-BRAMS has been used operationally by the Brazilian Center for Weather Prediction and Climate Studies (CPTEC, http://meioambiente. cptec.inpe.br) since 2003 and as a research tool by several groups around the world (e.g., Marécal et al, 2007Marécal et al, , 2010Longo et al, 2009;Landulfo et al, 2009;Arteta et al, 2009a, b;Liu et al, 2010;Ramos, 2006;Gevaerd, 2005;Herrmann, 2004;Gácita, 2011;Munchow, 2008;Hernández, 2010;Alonso, 2011), which demonstrates its good performance.…”
Section: K M Longo Et Al: the Chemistry Catt-brams Model (Ccatt-brmentioning
confidence: 99%
“…Such particle and molecular scale processes are poorly integrated into larger cloud and climate scale models, that generally have poorly constrained ice surface interaction schemes (Marécal et al, 2010). Furthermore the bundling of complex microphysical chemistry into parameters like surface tension can result in errors from oversimplification (Prisle et al, 2012).…”
Section: E S Thomson Et Al: Collision Dynamics and Uptake Of Watermentioning
confidence: 99%